Kõnekeskuse lateralisatsioon ja kaugtulemused erineva vaskulaarse alatüübiga perinataalse insuldiga lastel - Ilves, Nigul; Männamaa, Mairi; Laugesaar, Rael; Ilves, Norman; Loorits, Dagmar; Vaher, Ulvi; Kool, Pille; Ilves, Pilvi (Eesti Arst, 2022)
Eesti Arst 2022; 101(12):710